A tese da independência do banco central e a estabilidade de preços: uma aplicação do método Cukierman à história do FED - Sicsú, João (1996)
The paper aims to discuss the thesis that proposes the independence for central banks (ICB). With this aim, it applies the Alex Cukierman's method to measure the autonomy degree of Federal Reserve System in some important events from American monetary history. It verifies if the autonomy degree of the U.S. monetary authorities is correlated to the inflation rates of each event. Having calculated this correlation, the article debates on validity of ICB thesis.